2014
DOI: 10.1021/ac403931r
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Approach for Quantitative Imaging of Phospholipids Using Nanospray Desorption Electrospray Ionization Mass Spectrometry

Abstract: Mass spectrometry imaging (MSI) has been extensively used for determining spatial distributions of molecules in biological samples, and there is increasing interest in using MSI for quantification. Nanospray desorption electrospray ionization (nano-DESI) is an ambient MSI technique where a solvent is used for localized extraction of molecules followed by nanoelectrospray ionization. Doping the nano-DESI solvent with carefully selected standards enables online quantification during MSI experiments. In this proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
108
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 74 publications
2
108
1
Order By: Relevance
“…While variation in extraction efficiency across brain tissue has been found to be statistically negligible compared to that of recorded signal level for brain tissue, it is likely not the case for all samples. 47 In fact, a recent letter by Moench et al 28 reported variability in LESA extraction efficiencies when sampling from different organs in rat tissue. Thus, variable extraction efficiencies might be expected in other direct liquid extraction approaches and it would inhibit their ability to perform quantitative analyses.…”
mentioning
confidence: 99%
“…While variation in extraction efficiency across brain tissue has been found to be statistically negligible compared to that of recorded signal level for brain tissue, it is likely not the case for all samples. 47 In fact, a recent letter by Moench et al 28 reported variability in LESA extraction efficiencies when sampling from different organs in rat tissue. Thus, variable extraction efficiencies might be expected in other direct liquid extraction approaches and it would inhibit their ability to perform quantitative analyses.…”
mentioning
confidence: 99%
“…136 Using nano-DESI, Lanekoff et al have extended this approach to Q-MSI of endogenous PC species in rat brain tissue by adding two PC standards to the extraction solvent. 135 The two internal standards bracket the range of acyl chain lengths in endogenous PC species, which accounts for the effect of the chain length on the ionization efficiency of individual PC species using carbon factors (CF) given by Eq. 2: 135 CFPC=CFstd+γ×ΔNC In Eq.…”
Section: Matrix Effects and Quantificationmentioning
confidence: 99%
“…135 The two internal standards bracket the range of acyl chain lengths in endogenous PC species, which accounts for the effect of the chain length on the ionization efficiency of individual PC species using carbon factors (CF) given by Eq. 2: 135 CFPC=CFstd+γ×ΔNC In Eq. 2, the carbon factor for the standard (CF std ) is set to 1, γ is a factor that accounts for the effect of chain length on the ionization efficiency, and ΔN C is the difference between the number of carbons in the fatty acid chains of the endogenous PC and number of carbon atoms in the tail groups of the standard.…”
Section: Matrix Effects and Quantificationmentioning
confidence: 99%
“…In a different MSI study, quantitative nano-DESI imaging was suggested as a promising tool for accurate localization and relative quantification of analytes within heterogeneous tissue sections. 95 Lanekoff et al have shown in a proof of principle study that shotgun-like quantitation of endogenous phospholipids in different brain tissue sections can be possible by using 2 phosphatidylcholine standards in the nano-DESI solvent for simultaneous imaging and quantitation of 22 endogenous phosphatidylcholine species observed in MSI. 95 A different strategy that could improve quantitation in targeted studies by reducing matrix interferences is the coupling of an ambient-MSI technique with post ionization separation by IMS.…”
Section: Healthmentioning
confidence: 99%
“…95 Lanekoff et al have shown in a proof of principle study that shotgun-like quantitation of endogenous phospholipids in different brain tissue sections can be possible by using 2 phosphatidylcholine standards in the nano-DESI solvent for simultaneous imaging and quantitation of 22 endogenous phosphatidylcholine species observed in MSI. 95 A different strategy that could improve quantitation in targeted studies by reducing matrix interferences is the coupling of an ambient-MSI technique with post ionization separation by IMS. This allows imaging contrast enhancement through improved selectivity and signal-to-noise ratio by separating isobaric interferences.…”
Section: Healthmentioning
confidence: 99%